Pay discrimination revisiting the concept and international perspectives - Thompson, John Mark (Institute of Development and Labour Law, 2021)
Sex based wage discrimination has received much attention especially in the late seventies and throughout the eighties. South Africa has had pay equality provisions in place since 1980 and specific legislation in 1988. Although no comprehensive gender based wage study exist prior to 1980, international surveys in those countries indicates that large wage gaps between the income of men and women existed. This paper deals with possible reasons for gender bias perceptions and historical perceptions. The international perspective is dealt with on a comparative basis and possible reasons for success and failures are addressed. The previous government's race discrimination policies had direct bearing; not only on the race disparities but on sex based wage inequality. Black people were barred from occupying certain positions in the public service. Black women were, therefore, effectively prevented from entering the higher income job market. This resulted in a concentration of black women in the lower income categories of work ie, domestic and home related work. To measure the pay inequality, one has to have a comparator and this sometimes proves to be difficult. Women being concentrated in, for instance domestic jobs, have no male comparator to prove the existence of sex discrimination. The tendency throughout the world is for employers to concentrate women into a job category and rate that specific job low, thereby paving the way for lower wages. A directive was introduced by the Treaty of Rome whereby equal remuneration for jobs of equal value was to be enforced. Women were put in a position to challenge the neutrality of a job evaluation systems. In terms thereof women could challenge the pay structure by challenging the gender neutrality of the job evaluation study. The vital elements in conducting an action of this nature are discussed in the South African paradigm with reference to foreign experiences. Although no specific equal pay legislation exists, the Labour Relations Act of 1995, prohibits direct and indirect sex discrimination. This legislation is in line with international criteria and it is submitted that the prohibition includes equal pay for work of equal value. The defences raised by employers in foreign countries are discussed, although the applicability thereof remains uncertain. The Green Paper of Employment and Occupational Equity has been published. The Equal Pay issue has been identified as requiring attention. Interviews with NALEDI have indicated that the issues still have to be formalised before negotiations between trade unions, employers and the government are to commence. The international arena has provided a fruitful setting for gender equality, and although the success has been limited, we expect South Africa to draw from the experiences. Legislation in this regard is not expected before the later part of 1998. There are many academics, feminists and gender equality activists eagerly awaiting the publication of the Employment and Occupational Equity Act. Some points are made which are vital for effective legislation. On the other hand, the ineffectively of legislation in this field has been proved repeatedly in other countries.